2010
DOI: 10.1136/adc.2009.182162
|View full text |Cite
|
Sign up to set email alerts
|

Leak and obstruction with mask ventilation during simulated neonatal resuscitation

Abstract: Mask ventilation during simulated neonatal resuscitation was often hampered by large leaks at the face mask. Moderate airway obstruction occurred frequently when effort was taken to minimise leak. Training in mask ventilation reduced mask leak but should also focus on preventing airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 15 publications
5
88
0
Order By: Relevance
“…19 A recent systematic review and metaanalysis noted that compared with no intervention (eg, a control group or preintervention assessment), simulationbased training was effective in improving the knowledge, skills, and behaviors of health care professionals. 1 In pediatrics, simulation has been effectively used to teach neonatal [20][21][22] and pediatric resuscitation, 3,6,7 crisis resource management, 8,9,20,[23][24] anesthesia, [25][26][27] procedural skills 5,[28][29][30] (eg, gynecology examination, airway management), and surgical skills [31][32][33] (eg, endoscopy and minimally invasive surgery). Although the scope of simulation-based education in pediatrics is growing, few comparative studies have helped to clearly define the optimal instructional design features of effective pediatric SBEI.…”
Section: Categories Of Sbr Research On the Efficacy Of Simulation As mentioning
confidence: 99%
“…19 A recent systematic review and metaanalysis noted that compared with no intervention (eg, a control group or preintervention assessment), simulationbased training was effective in improving the knowledge, skills, and behaviors of health care professionals. 1 In pediatrics, simulation has been effectively used to teach neonatal [20][21][22] and pediatric resuscitation, 3,6,7 crisis resource management, 8,9,20,[23][24] anesthesia, [25][26][27] procedural skills 5,[28][29][30] (eg, gynecology examination, airway management), and surgical skills [31][32][33] (eg, endoscopy and minimally invasive surgery). Although the scope of simulation-based education in pediatrics is growing, few comparative studies have helped to clearly define the optimal instructional design features of effective pediatric SBEI.…”
Section: Categories Of Sbr Research On the Efficacy Of Simulation As mentioning
confidence: 99%
“…8,9,11 Sometimes, to prevent mask leak, caregivers press too firmly, which can cause obstruction. 26 With the use of a nasal tube, although compressive forces are not involved, leak may occur from the contralateral nostril or as a result of an open mouth and inadequate jaw thrust, …”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Mask leak and obstruction during mask PPV are often not recognized. 8,9,11 They may compromise the delivery of the set positive end-expiratory pressure (PEEP) and appropriate tidal volumes, resulting in delayed establishment of effective gas exchange. 8,9 Current guidelines for the stabilization of premature infants in the DR recommend the use of an appropriately sized face mask and the provision of PEEP if available.…”
mentioning
confidence: 99%
“…Adequate noninvasive ventilation using a mask as interface plays an important role in neonatal resuscitation [1,2,3,4]. It has been suggested that a respiratory function monitor as a feedback device during neonatal resuscitation will be helpful and can inform the clinician about the tidal volumes delivered and whether mask leak occurs [5].…”
Section: Introductionmentioning
confidence: 99%